EFFECT OF CARBON NANOTUBES ON THE ELECTRICAL PROPERTIES OF THE POLYMERIC COMPOSITES (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2019)
Experimental study of single-wall carbon nabotubes (CNT) effect on the electrical properties of polymeric composite materials based on epoxy matrix has been carried out. Direct-current (DC) as well as alternating-current (AC) electrical conductivity of nanocomposites with different CNT concentrations have been investigated in the temperature interval from 293 K to 373 K. Measurements of Seebeck coefficient confirm n-type conductivity of composite with CNTs. Percolation threshold of the composite material under study has been estimated. It has been found that addition of single-wall CNT at low concentration causes hysteresis of current-voltage characteristics and the temperature dependences of electrical conductivity as well as its anisotropy in the samples under study. No noticeable frequency dependence of the AC electrical conductivity has been found in the frequency range from 100 Hz to 300 kHz.